Pakistan [videorecording (DVD)] - Campbell, Luke; Gibson, Neil (Destination travel guide series., 2009)
Pakistan contains some of Asia's most dynamic landscapes, as well as a kaleidoscope of cultures and ancient civilizations. Neil Gibson begins his journey in the bustling port city of Karachi, then travels north to the Sufi city of Multan where he arrives in time for the Urs Festival. He then visits the cultural and artistic capital of Pakistan, Lahore, before journeying to the frontier city of Peshawar and the legendary Khyber Pass. Then it's on to the exotic valley of Chitral and the mountain town of Gilgit for the Ashura festival, a Shi'ite festival commemorating the death of Iman Hussein, the last descendant of the prophet Mohammed. He ends his journey trekking in the Hunza Valley.